Hemispheric Indigeneities : Native Identity and Agency in Mesoamerica, the Andes, and Canada - Langer, Erick Detlef; Santoro, Milena, 1965- (Book collections on Project MUSE., 2018)
"Hemispheric Indigeneities: Native Identity and Agency in Mesoamerica, the Andes, and Canada is a critical anthology that brings together indigenous and non-indigenous scholars specializing in the Andes, Mesoamerica, and Canada. The overarching theme of this volume is the changing understanding of indigeneity from first contact to the contemporary context in three of the world's major regions of indigenous peoples, as well as the deployment of the idea of indigeneity over time both to deny and to reconstruct a sense of identity and sovereignty"--